2021
DOI: 10.4049/jimmunol.2000083
|View full text |Cite
|
Sign up to set email alerts
|

E3 Ubiquitin Ligase RNF114 Inhibits Innate Immune Response to Red-Spotted Grouper Nervous Necrosis Virus Infection in Sea Perch by Targeting MAVS and TRAF3 to Mediate Their Degradation

Abstract: RIG-I–like receptor (RLR)–mediated antiviral signaling is critical to trigger the immune response to virus infection; however, the antiviral responses are also tightly regulated to avoid uncontrolled production of type I IFN by various mechanisms, including ubiquitination. In this study, an E3 ubiquitin ligase ring finger protein 114 (RNF114) from sea perch (Lateolabrax japonicus) (LjRNF114) was identified as a suppressor of RLR signaling pathways during red-spotted grouper nervous necrosis virus (RGNNV) infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Several studies also identified that the RNF114/LjRNF114 directly associates with MAVS and targets it for proteasomal degradation via K27-linked ubiquitination to inhibit RLR-mediated antiviral signaling. 243 , 244 However, Rnf114 −/− mice failed to display enhanced resistance to RNA virus infection. Based on the above findings, further investigation is needed to determine the paradoxical roles of RNF114 in RLR signaling pathways.…”
Section: Rnf Family Proteins In Viral Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies also identified that the RNF114/LjRNF114 directly associates with MAVS and targets it for proteasomal degradation via K27-linked ubiquitination to inhibit RLR-mediated antiviral signaling. 243 , 244 However, Rnf114 −/− mice failed to display enhanced resistance to RNA virus infection. Based on the above findings, further investigation is needed to determine the paradoxical roles of RNF114 in RLR signaling pathways.…”
Section: Rnf Family Proteins In Viral Infectionmentioning
confidence: 99%
“…A recent study, controversial to a previous study, revealed that the LjRNF114, RNF114 from Lateolabrax japonicus , interacts with TRAF3 and transfers the K48-linked ubiquitination to TRAF3 for proteasomal degradation to modulate the RLR-mediated antiviral signaling negatively. 236 , 243 Interestingly, their study also indicated that Red-Spotted grouper nervous necrosis virus (RGNNV) infection enhances the expression of LjRNF114, suppressing the RLR-dependent IFN production, thus potentiating the RGNNV replication in a positive feedback manner. This report provided a potential target at LjRNF114 for a prospective therapeutic strategy against nervous necrosis virus infection, which causes more than 90% mortality in the larval stage of fish.…”
Section: Rnf Family Proteins In Viral Infectionmentioning
confidence: 99%
“…Multiple molecules act as negative regulators of type I IFN production by regulating the stability of MAVS along with the formation of the MAVS/TRAF3 complex in a variety of manners. For instance, the E3 ubiquitin ligase RNF114 inhibits the innate immune response against the red-spotted grouper nervous necrosis viral infection by targeting the interaction between TRAF3 and MAVS in sea perch [ 10 ]. The hereditary hemochromatosis protein HFE inhibits the production of type I IFN signaling by targeting the SQSTM1-mediated autophagic degradation of MAVS [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…As an excellent in vitro platform, fish cell lines have been widely applied to the study of virology, immunology, toxicology, preservation of germplasm resources, gene screening and functional analysis (Collet et al., 2018; Liu et al., 2020; Ruiz‐Palacios et al., 2020). For instance, fathead minnow (FHM) cell line was applied to the propagation of multiple fish viruses, including viral haemorrhagic septicaemia virus (VHSV), nervous necrosis virus (NNV) and infectious pancreatic necrosis virus (Huang et al., 2018; Lorenzen et al., 1999; Zhang, Li, et al., 2019); Lateolabrax japonicus brain cell line, derived from the brain of sea perch, was used for studying the interaction between NNV and sea perch (Jia et al., 2016; Xiang et al., 2021); and Fundulus heteroclitus brain cell line, pearl gentian grouper gill cell line and Trachinotus ovatus kidney cell line were applied to investigate the toxicity of PS‐100, Cd, Cu and Hg, respectively (Ruiz‐Palacios et al., 2020; Xu et al., 2021; Zhou et al., 2017). Since the establishment of the first fish cell line RTG‐2 in 1962, more than 880 fish cell lines have been established to date (Robin et al., 2020; Wolf & Quimby, 1962).…”
Section: Introductionmentioning
confidence: 99%